Efficacy of Rasayana Avaleha as adjuvant to radiotherapy and chemotherapy in reducing adverse effects - Vyas, Purvi (Medknow Publications Pvt Ltd, 2010)
Cancer is the most dreadful disease affecting mankind. The available treatments such as chemotherapy and radiotherapy have cytotoxic effects, which are hazardous to the normal cells of the patient, causing many unnecessary effects. This further leads to complications of the therapy, impaired health, and deterioration of quality of life, resulting in mandatory stoppage of the treatment. In the present study, the efficacy of an Ayurvedic formulation, Rasayana Avaleha, has been evaluated as an adjuvant medication to modern radiotherapy and chemotherapy. A total of 36 cancer patients were registered in this trial and were divided into two groups, group A and group B. In group A, the patients were treated with radiotherapy and chemotherapy along with adjuvant Rasayana Avaleha (RT + CT + RA), while in group B only radiotherapy and chemotherapy (RT + CT) were given, as the control group. After assessing the results, it was observed that Rasayana Avaleha gave better results in controlling the adverse effect of chemotherapy and radiotherapy in comparison with the control group. Therefore, Rasayana Avaleha has proved to be an effective adjuvant therapy in protecting patients from the adverse effects of chemotherapy and radiotherapy.